-9x +y=12 and 2x+4y=-28

1 answer

To solve this system of equations by elimination, we can first multiply the first equation by 4 to match the coefficients of y:

-36x + 4y = 48
2x + 4y = -28

Next, we can subtract the second equation from the first equation:

-36x + 4y - 2x - 4y = 48 - (-28)
-38x = 76
x = -2

Now that we have found x, we can substitute it back into either original equation to solve for y. Let's use the first equation:

-9(-2) + y = 12
18 + y = 12
y = -6

Therefore, the solution to the system of equations is x = -2 and y = -6.